Surface topography measurement of microstructures near the lateral resolution limit via coherence scanning interferometry. (May 2022) - Sun, Yifeng; Gao, Zhishan; Ma, Jianqiu; Zhou, Juntao; Xie, Pengfei; Wang, Lingjie; Lei, Lihua; Fu, Yunxia; Guo, Zhenyan; Yuan, Qun
Highlights: Surface topography measurement near CSI lateral resolution limit is realised. Characteristics of anomalous coherence signals are analysed. Binarization method based on edge localization is proposed. A new form of the Morlet wavelet family is constructed. Measurements are consistent with SEM results. Abstract: As a non-destructive method, coherence scanning interferometry is widely utilized for surface topography measurement of step microstructures in optical and integrated circuit fields. The measurements are always implemented near the lateral resolution limit of the system because the critical dimension of these microstructures is at the micron or sub-micron scale. However, in this case, not only is the image of microstructures blurred, but also the diffraction effects distort the measured topography near the step edges. The magnitude of distortion at a certain position appears to be related to its distance from the edges and the duty cycle of the microstructures. Therefore, it is necessary, although difficult, to improve the accuracy of topography measurement for microstructures if their images are blurred owing to the lateral resolution limit. When located far away from the step edges of microstructures, the coherence signals are normal and contain a single envelope with its peak corresponding to the surface height. However, the anomalous coherence signals containing two envelopes appear near the step edges. The peaks of these envelopes correspond to the top and bottom surfaces of step structures, thus distorting the coherence peak detection for topography measurement. Therefore, the primary issue is the determination of the correct envelope in the anomalous coherence signals that is achieved by distinguishing the current surface of step structures for each position. In this paper, we propose a binarization method based on edge localization to achieve surface distinguishment through the analysis of the contrast and intensity of the coherence signals. After determining the correct envelope, we construct a new form of wavelet family and employ the Morlet wavelet transform to calculate a split point for dividing the anomalous coherence signals. Finally, the effective coherence signals corresponding to the correct envelope are extracted. Surface topography measurement of the nanopillars on the metasurface is obtained from the extracted signals. These nanopillars are distributed with a varying duty cycle and their diameters range from 590 to 1350 nm, near the lateral resolution limit of 501.9 nm of the system. The topography of nanopillars is recovered from the field of view, while the diameter and height of different types of nanopillars are measured. The mean value and standard deviation of these two parameters are consistent with the results obtained via scanning electron microscopy.